Neurological Complications with COVID-19: A Contemporaneous Review - Maramattom, Boby Varkey (Ann Indian Acad Neurol, 2020)
The COVID-19 pandemic is raging across the world, affecting 212 Countries and Territories around the world. It has infected more than 3.7 million people with a mortality rate of around 7%. Although the causative virus, the SARS-CoV-2 is primarily a respiratory pathogen, recent observational studies have documented a high rate of neurological complications associated with COVID-19. We searched PubMed databases from December 01, 2019 to June 9, 2020 for articles published on “COVID 19” OR “coronavirus” with targeted search words. We also search preprint servers for neurological complications of COVID-19. Neurological manifestations are seen in around 36%–45% of patients with COVID-19 and can involve almost every part of the central nervous system (CNS) from the hemispheres, cranial or peripheral nerves, spinal cord, and muscle. The mechanisms vary from direct viral invasion of the CNS, to a dysregulated host immune response to molecular mimicry to multiorgan dysfunction. In many patients, neurological manifestations preceded other systemic features or the diagnosis of COVID-19. Sick patients with COVID-19 will require ICU care and many patients may present first to the neurocritical care ICU and receive a diagnosis of COVID-19 later. Hence, it is important for all healthcare personnel to be aware of the myriad neurological manifestations of this infection, so as to initiate appropriate infection control practices and refine investigation and treatment protocols.